Fluorescent X-ray analysis of silver halide - ASADA, Eiichi; YABE, Kotaro; KUNIMINE, Noboru; UGAZIN, Hisakazu (BUNSEKI KAGAKU, 1964)
The determination of silver halide in its powdery preparations, photographic emulsions and photographic films was investigated by fluorescent X-ray analysis. (1) The fluorescent X-ray intensity had no distinction between solid solution and mixture of silver halide, and, consequently, the calibration curves prepared for the both states coincided well. (2) Silver and bromine in AgBr-AgI emulsion were determined by the dilution method for the concentration of Ag or Br above 200 mg, /em. 10 g. (3) The thickness of emulsion layer of commercial films was not required to be taken into consideration and silver halide could be determined with good precision. (4) The difference of photographic film base had no influence on analytical result. (5) The accuracy of fluorescent X-ray analysis of photographic film was nearly equal to that of the result of chemical analysis, but the time for an analysis and the amount of sample taken were diminished extremely.